ON THE ANALYSIS OF COVID-19 TRANSMISSION IN WUHAN, DIAMOND PRINCESS AND JAKARTA-CLUSTER - Soewono, Edy (Communication in Biomathematical Sciences, 2020)
The whole world has been recently shocked by the massive spread of Covid-19 without any sign of when it will end. This phenomenon of this scale is understood as a plague that has never been happening in a lifetime. Almost all countries do not have proper preparedness when positive cases are found in a region. In a relatively short time, cases then spread quickly, and panic broke out in the community. With the rapid human to human transmission, and there is no vaccine available, the only way to control the spread of the disease is by implementing a contact tracing and isolation policy. The fact indicated that health officials in many affecting countries have difficulty in detecting individuals who are potentially exposed to the virus. The success of controlling the disease is very much dependent on the ability of the health authority in tracking and isolating the infected and the suspected cases. A transmission model for Covid-19 transmission in the form of SEIR is chosen to fit with the cases in Wuhan, Diamond Princess, and Jakarta-cluster. These cases represent the transmission in a large city, a relatively restricted and dense area, and a small cluster, respectively. The basic reproductive ratio and the infection rate are obtained based on the cumulative data for each case. These indicators can be used for predicting the progress of transmission for similar cases. A simple model for estimating the completing time of contact tracing and isolation is constructed in the form of a differential operator on the cumulative case. This operator represents the number of daily new infected cases. It is shown that for the case of Wuhan, the completing time for contact tracing and isolation is 55 days. This result is important for analyzing the intervention strategy of Covid-19 in an affected region.